Prioritizing Higher Order Thinking Skills (HOTS) Based on the 2013 Curriculum on Language Learning Evaluation at the Tertiary Level Education in Indonesia - Neni Afrida Sari Harahap; Muhammad Natsir (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
The 2013 Curriculum is designed to revise many aspects of language learning for tertiary level students which is related to international evaluation standard based on Higher Order Thinking Skills (HOTS). This study investigates the percentage of HOTS used in English learning evaluation and its implications to language learners at tertiary level education in Indonesia. By conducting a descriptive qualitative method, an English textbook of 2013 Curriculum for the tenth grade of tertiary level students in Indonesia is analyzed in this research. The data collected by using checklist at four steps of selecting, classifying, coding and presenting percentage of HOTS. The result shows that HOTS is prioritized in the textbook learning evaluation in which the questions are dominated by Higher Order Thinking Skills on C4, C5 and C6. Evaluating level (C5) plays the most dominant percentage (38.57%) in the level of questions from the textbook. As the implications, HOTS should be prioritized at tertiary level education in Indonesia because of these reasons: (1) The needs of students qualifications required by challenges in this Industrial Revolution 4.0 of 21st century to have the opportunities getting job/professions in the work places, (2) The target of Curriculum to gain Students Competence on: Critical Thinking, Creativity, Collaboration and Communication must be achieved, and (3) HOTS should be applied in any disciplines of subject matter in Indonesia since the primary level up to the tertiary ones because it must be started earlier to grasp the result faster.